Evaluation of Epstein-Barr virus expression in oral squamous cell carcinomas - Saeedeh Khalesi; Laleh Maleki; Farzad Ghapani (Wolters Kluwer Medknow Publications, 2022)
Background: Oral squamous cell carcinoma (OSCC) is one of the most common cancers. Epstein-Barr virus (EBV) has been related to throat-esophageal and gastric cancers. The aim of this study was to evaluate the prevalence of EBV in OSCC. Materials and Methods: This descriptive-analytical cross-sectional study was performed on 48 samples recorded in the archives of the Oral Pathology Department of Isfahan Dental School with definitive diagnosis of OSCCs prepared by excisional biopsy. Samples were selected in different age groups, locations, and genders. The grade of the tumor malignancy was determined based on Annreroth's classification. The EBV expression was determined by immunohistochemical (IHC) staining. The data were entered into SPSS software and statistically analyzed by t-test, Chi-square, and Fisher's exact test. Significance level was considered P < 0.05. Results: IHC staining for EBV was positive in 25 samples (52%). There was no significant relationship between EBV expression and mean age, gender, clinical feature, and grade of tumor differentiation (P > 0.05). A significant difference was observed between the EBV expression and location (P = 0.035). Furthermore, a significant difference was observed between the grade of tumor and staining intensity distribution index of EBV (P = 0.005). Conclusion: EBV expression was observed in most of the OSCCs, especially in poorly differentiated tumors. The pathogenesis of OSCCs may be related with EBV. OSCCs in buccal mucosa and floor of the mouth have more frequently of EBV expression. Future studies on the mechanisms of EBV and their role in OSCC are required with larger sample sizes.